2017
DOI: 10.1016/j.foodhyd.2016.10.029
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol encapsulation in core-shell biopolymer nanoparticles: Impact on antioxidant and anticancer activities

Abstract: Zein/pectin core-shell nanoparticles with average diameter of about 235 nm and polydipersity index (PDI) of 0.24 were developed to encapsulate, protect and deliver resveratrol. Biopolymer nanoparticles could be formed containing up to 10.2% (w/w) resveratrol, with a particle yield of 91.7% and a resveratrol loading efficiency of 77.9%. The nanoparticles formed were spherical and had good redispersibility in aqueous solutions. The encapsulated resveratrol had a higher in vitro antioxidant activity than free res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
90
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 260 publications
(102 citation statements)
references
References 45 publications
10
90
2
Order By: Relevance
“…Due to its ability to form nanoparticles, zein has been used to provide protection, stability, and as a delivery system to bioactive compounds (Wang et al., ). Among the bioactive compounds that have been encapsulated in zein nanoparticles and their respective obtention methods of obtaining are the following: resveratrol by antisolvent precipitation (Huang et al., ); rutin by antisolvent precipitation (Zhang, & Han, ); quercetagetin by antisolvent coprecipitation (Chen et al., ); curcumin by antisolvent precipitation and liquid–liquid dispersion (Hu, Wang, Fernandez, & Luo, ; Xue et al., ; Zou et al., ); vitamin A by phase separation (Park, Park, & Kim, ); vitamin D3 by phase separation (Luo, Teng, & Wang, ); procyanidins by liquid–liquid dispersion (Zou, Li, Percival, Bonard, & Gu, ), Tangeretin by liquid–liquid dispersion (Chen, Zheng, McClements, & Xiao, ); lutein by liquid–liquid dispersion (Chuacharoen & Sabliov, ), and quercetin by the desolvation procedure of an hydroalcoholic solution (Penalva, González‐Navarro, Gamazo, Esparza, & Irache, ). However, the previously noted methods by which zein nanoparticles with bioactive compounds have been obtained do not ensure that the entire solvent is removed from the nanoparticles, and an additional process is used, such as lyophilization, to obtain them in the form of powder, for which electrospraying comprises a technique that eliminates the entirety of the solvent and it can be obtained in powder in a single step.…”
Section: Introductionmentioning
confidence: 99%
“…Due to its ability to form nanoparticles, zein has been used to provide protection, stability, and as a delivery system to bioactive compounds (Wang et al., ). Among the bioactive compounds that have been encapsulated in zein nanoparticles and their respective obtention methods of obtaining are the following: resveratrol by antisolvent precipitation (Huang et al., ); rutin by antisolvent precipitation (Zhang, & Han, ); quercetagetin by antisolvent coprecipitation (Chen et al., ); curcumin by antisolvent precipitation and liquid–liquid dispersion (Hu, Wang, Fernandez, & Luo, ; Xue et al., ; Zou et al., ); vitamin A by phase separation (Park, Park, & Kim, ); vitamin D3 by phase separation (Luo, Teng, & Wang, ); procyanidins by liquid–liquid dispersion (Zou, Li, Percival, Bonard, & Gu, ), Tangeretin by liquid–liquid dispersion (Chen, Zheng, McClements, & Xiao, ); lutein by liquid–liquid dispersion (Chuacharoen & Sabliov, ), and quercetin by the desolvation procedure of an hydroalcoholic solution (Penalva, González‐Navarro, Gamazo, Esparza, & Irache, ). However, the previously noted methods by which zein nanoparticles with bioactive compounds have been obtained do not ensure that the entire solvent is removed from the nanoparticles, and an additional process is used, such as lyophilization, to obtain them in the form of powder, for which electrospraying comprises a technique that eliminates the entirety of the solvent and it can be obtained in powder in a single step.…”
Section: Introductionmentioning
confidence: 99%
“…Resveratrol in kafirin, kafirin/β‐Lg and kafirin/casein nanoparticles showed significantly less ( P < 0.05) scavenging capacities than unencapsulated resveratrol, due to that encapsulation in the hydrophobic core of the particles limited the polyphenol interaction with hydrophilic ABTS˙ + (Tai et al ., ). Our results contradict previous reports that resveratrol encapsulated in zein/pectin particles and liposomes had greater ABTS˙ + scavenging capacity than resveratrol in ethanol (Vanaja et al ., ; Huang et al ., ). The reduction in ABTS˙ + scavenging capacity of resveratrol at 20 μg mL −1 was consistent with its hydrophobic environment in order kafirin/β‐Lg > kafirin/casein > kafirin (Fig.…”
Section: Resultsmentioning
confidence: 97%
“…ABTS˙+ and DPPH˙scavenging activities of 166 lg mL À1 resveratrol in ethanol and in kafirin, kafirin/b-Lg and kafirin/casein particles were estimated according to the method of Huang et al (2017). ABTS cation radicals were prepared by mixing 4.9 mmol L À1 potassium persulfate with 7 mmol L À1 ABTS in dark and diluted to an absorbance of 0.7.…”
Section: Antioxidant Activitymentioning
confidence: 99%
“…Bioactivity and bioavailability enhancement through encapsulation of zein protein particles has also been achieved with other nutraceuticals such as i) resveratrol, it was shown that encapsulated resveratrol had stronger antioxidant and anticancer activity than free resveratrol . ii) Folic acid, the encapsulation of folic acid resulted in improved pharmacokinetics (Figure b) and a twofold increase in its oral bioavailability .…”
Section: Emerging Application Of Functional and Engineered Food Colloidsmentioning
confidence: 91%